2021
DOI: 10.3390/ijerph18042051
|View full text |Cite
|
Sign up to set email alerts
|

“We All Really Need to just Take a Breath”: Composite Narratives of Hospital Doctors’ Well-Being during the COVID-19 Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic poses a challenge to the physical and mental well-being of doctors worldwide. Countries around the world introduced severe social restrictions, and significant changes to health service provision in the first wave of the pandemic to suppress the spread of the virus and prioritize healthcare for those who contracted it. This study interviewed 48 hospital doctors who worked in Ireland during the first wave of the pandemic and investigated their conceptualizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 51 publications
2
118
0
Order By: Relevance
“…Studies have shown that more than half of the surveyed population considered the vaccine to be effective. From an existential point of view, the above opinion raises hope for an improvement in the psychosocial situation of doctors, who, according to other studies, experienced a deterioration in mental well-being due to isolation, anxiety, emotional exhaustion and poor social support during the pandemic [ 13 ]. The above thesis is confirmed by research conducted among doctors in Germany [ 14 ], where their existential disadvantage was observed during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that more than half of the surveyed population considered the vaccine to be effective. From an existential point of view, the above opinion raises hope for an improvement in the psychosocial situation of doctors, who, according to other studies, experienced a deterioration in mental well-being due to isolation, anxiety, emotional exhaustion and poor social support during the pandemic [ 13 ]. The above thesis is confirmed by research conducted among doctors in Germany [ 14 ], where their existential disadvantage was observed during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting studies on workload of doctors working in surgery. Non-urgent elective operations have been cancelled in order to support the wider COVID-19 response and surgical staff have been redeployed throughout the hospital [ 27 , 28 ]. Though this may appear to have primarily reduced the workload of surgeons, the changing work environment has caused worry for surgeons due to delay in surgical services, fewer training opportunities, and redeployment to critical care or medicine [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Workload for junior and middle-grade doctors may have increased due to redeployment to manage the increased demand from COVID-19 patients [ 13 , 28 ]. For doctors redeployed to intensive treatment units (ITUs), workload was high, with management of multiple unwell patients, demanding rotas, and filling in for absenteeism or unwell staff during the pandemic [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As employee wellbeing is one of the sustainability-related goals of most organizations, it is necessary to investigate how to enhance healthcare workers' wellbeing during the COVID-19 pandemic, which is of great significance for organizations to continue to meet their sustainability goals in the face of an external crisis [15,16]. Since leaders are generally viewed as agents of organizations, leadership styles and behaviors will have a great influence on their subordinates' emotional experience and psychological status and affect their wellbeing [17,18].…”
Section: Introductionmentioning
confidence: 99%